Exploration of Change Management Process in the Global Project - Łatoszyńska, Anna (Eksploracja roli lidera w zarządzaniu zmianą w projekcie o zasięgu globalnym, 2025)
The article discusses the complexity of change management in a global company, focusing on e-procurement tool deployment. It analyses the challenges and drivers of change, emphasizing the supportive role of the leader as the most important in the process of successful implementation of the changes. In-depth interviews with business leaders revealed three categories of key factors of the implementation of e-procurement tool: people, technology, and process. The study provides practical guidelines for improving change management strategies in global projects.
Quote as: Łatoszyńska, A. (2025). Exploration of Change Management Process in the Global Project. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 156-167). Publishing House of Wroclaw University of Economics and Business.
Keywords: change management; business leaders interview; leadership role; e-procurement; zarządzanie zmianą; wywiady z liderami; role liderów